2011
DOI: 10.1007/s00216-011-5363-y
|View full text |Cite
|
Sign up to set email alerts
|

Advances in organic transistor-based biosensors: from organic electrochemical transistors to electrolyte-gated organic field-effect transistors

Abstract: Organic electronics have, over the past two decades, developed into an exciting area of research and technology to replace classic inorganic semiconductors. Organic photovoltaics, light-emitting diodes, and thin-film transistors are already well developed and are currently being commercialized for a variety of applications. More recently, organic transistors have found new applications in the field of biosensors. The progress made in this direction is the topic of this review. Various configurations are presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
194
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 265 publications
(195 citation statements)
references
References 82 publications
1
194
0
Order By: Relevance
“…Actually, an EGOFET looks like an OECT (organic electrochemical transistor) [10][11][12][13][14][15][16]. However, in an OECT, the on/off switch is produced by electron transfer from the electrolyte and the semiconductor (doping/de-doping) [8], whereas only capacitive processes occur for EGOFETs but no charge transfer.…”
Section: Egofetsmentioning
confidence: 99%
See 2 more Smart Citations
“…Actually, an EGOFET looks like an OECT (organic electrochemical transistor) [10][11][12][13][14][15][16]. However, in an OECT, the on/off switch is produced by electron transfer from the electrolyte and the semiconductor (doping/de-doping) [8], whereas only capacitive processes occur for EGOFETs but no charge transfer.…”
Section: Egofetsmentioning
confidence: 99%
“…As shown on Figure 2, when the gate is (for example) negatively polarized, the excess of electrons at the gate surface produces the accumulation of cations at the gate/electrolyte interface; conversely, accumulation of anions at the electrolyte/semiconductor interface produces accumulations of holes in the topmost layer of the semiconductor [17,18], which causes the OSC to become conducting. It has been shown that a significant double layer can form even for very low operating potentials, nevertheless sufficient to generate a locally high electrical field at the electrolyte/semiconductor interface, and therefore a high charge carrier density [8]. The electrolyte used can be polymers [19][20][21][22], ionic liquids [23][24][25] or ionic gels [16,[26][27][28][29].…”
Section: Egofetsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the ability of organic semiconductors to operate in aqueous environment and their proved biocompatibility [14][15][16] make them the ideal interface between electronics and biological systems. 17 However, despite quick advancements of organic bioelectronics in recent years, only few examples have been described about interfacing conducting polymers with living systems. In most cases, they are related to studies focused on cell adhesion, [18][19][20] measuring neuronal activity, 21 or developing sensors for toxicology.…”
Section: Apl Materials 3 014909 (2015)mentioning
confidence: 99%
“…
In recent years, organic electronic devices have become more and more popular, such as organic solar cell (OSC) [1][2][3][4], organic light emitting diode (OLED) [5][6][7] and organic thin film transistor (OTFT) [8][9][10][11] by virtue of their light weight, easy-processing and flexibility. As OTFT could be used as functional device or drive circuit to activate other devices [12,13], the development of OTFT becomes more urgent in practical applications.
…”
mentioning
confidence: 99%